PENGARUH PENGUMUMAN UPGRADE DAN DOWNGRADE BOND RATING TERHADAP ABNORMAL RETURN SAHAM DI BURSA EFEK INDONESIA (Studi Empiris pada Perusahaan yang Listing di Bursa Efek Indonesia tahun 2018-2019) - Indah Putri Indani; Maslichah Maslichah; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This study aims to determine the existence of significant stock abnormal returns around the announcement of bond rating upgrades and downgrades in companies that issue shares and bonds listed on the Indonesia Stock Exchange (BEI) in 2019. Information on upgrading and downgrade bond rating announcements is published by rating agencies, namely PT. Pefindo (PT. Pemeringkat Efek Indonesia). Data collection method used in this study is to use purposive sampling method in order to obtain a total sample of 11 companies. This research is an event study with 11 days of observation period that is 5 days before the announcement, 1 day during the announcement, and 5 days after the bond rating announcement. Research data and hypotheses in this study were analyzed using SPSS 16.0. The results of this study indicate that there is no significant abnormal return around the announcement of the bond rating upgrade and downgrade can be seen from the value of t AAR upgrade bond rating of -0.132 and the significance of t 0.898> 0.05, and the value of t AAR downgrade bond rating of 0.326 and Significance results t 0.751> 0.05. Keywords : abnormal return, upgrade bond rating, downgrade bond rating, stock returns, event study